Pulmonary malignant granular cell tumor - Jiang, Ming (BioMed Central, 2003)
BACKGROUND: Malignant granular cell tumor (MGCT) is a rare disease entity. Forty-one well-documented MGCTs have been reported in the world literature. CASE REPORT: This report describes a patient who presented with a MGCT of the lung and reviews the preoperative evaluation, pathologic features and differential diagnosis of the disease. This case represents the first report of resected primary pulmonary MGCT. CONCLUSIONS: Diagnosis of MGCT is based on histology of the primary tumor, immunohistochemistry, and exclusion of tumors that may mimic granular cell tumor.